Suplementasi bakteri asam laktat dalam mengendalikan infeksi bakteri Pseudomonas sp. pada ikan nila (Oreochromis niloticus): Supplementation of lactic acid bacteria in controlling bacterial infections of Pseudomonas sp. in Tilapia (Oreochromis niloticus) - Awang Andrian Sumarlan; Agustina; Gina Septiani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2023)
Bacterial disease in fish that is often a problem is caused by Pseudomonas sp. The purpose of this study was to examine the effect of supplementation with lactic acid bacteria on the body's resistance of tilapia infected with Pseudomonas sp. This research was conducted from March to April 2022 at the Laboratory of Microbiology and Aquaculture Biotechnology, Faculty of Fisheries and Marine Sciences, Mulawarman University. This study used a completely randomized design (CRD) with 4 treatments with different lactic acid bacteria and 3 replications of the same lactic acid bacteria. used, namely: P0 (PBS), P1 (Enterococcus feacalis), P2 (Lactobacillus plantarum), P3 (Lactococcus lactis) with a dose of 106 CFU/mL and mixed with 2% egg white given for 14 days. The results showed that lactic acid bacteria supplementation able to relieve clinical symptoms and anatomical pathology, increase survival compared to the control treatment in this study, the highest survival rate was 100% in the Enterococcus feacalis treatment. (P>0.05) and the lowest total colony average was 7.45 x 103 CFU/mL, namely the treatment with Enterococcus faecalis and the water quality parameters were still within normal limits.